The CIRCULAR pathway: a new educational methodology for exploratory circular value chain redesign - Garcia-Saravia Ortiz-de-Montellano, Cris; Ghannadzadeh, Ali; van der Meer, Yvonne (Frontiers in Sustainability, 2023)
The circular economy (CE) is gaining global relevance across countries and institutions as a tool to solve some of the most pressing global challenges derived from linear production and consumption systems. However, transitioning to a CE requires significant changes in how businesses and supply chains operate, including redesigning products, processes, and business models. These changes require that future professionals acquire knowledge and skills on the principles of CE, Life Cycle Thinking, and Systems Thinking. However, research on existing higher education programs signals a need for educational resources to develop these skills and knowledge in real-world settings. This paper outlines a new eight-step methodology to introduce students to the principles of CE through the exploratory redesign of a real-world product and value chain in a project-centered learning environment. This methodology was developed in four iterations and was used to teach 251 students from the BSc. Business Engineering at Maastricht University during the academic years 2020-2022. The findings indicate that this method supports students’ understanding of complexity, linearity, and the importance of systemic change across the entire value chain, as well as their critical thinking, problem-solving, and decision-making skills. The methodology provided in this paper supports and encourages educational bodies to implement CE education in their curricula.